Problematic of the functional structure of Slovene cities - Pak, Mirko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2004)
Slovene cities are subject of rapid spatial, structural and functional development. Ljubljana, the capital, is pointing out, where development differences are increasing in comparison to other Slovene cities. The article represents the processes of tertiarisation, spatial changes and changec in thefunctional structure of Slovene cities.
Keywords: mesta; urbana naselja; urbana geografija; raba prostora; mestni prostor; Slovenia; Slovenija